An oral fixed-dose combination of decitabine and cedazuridine in myelodysplastic syndromes: a multicentre, open-label, dose-escalation, phase 1 study. Issue 4 (April 2019) - Savona, Michael R; Odenike, Olatoyosi; Amrein, Philip C; Steensma, David P; DeZern, Amy E; Michaelis, Laura C; Faderl, Stefan; Harb, Wael; Kantarjian, Hagop; Lowder, James; Oganesian, Aram; Azab, Mohammad; et al.
Summary: Background: Decitabine, a DNA methyltransferase 1 inhibitor or DNA hypomethylating compound, is not readily orally bioavailable because of rapid clearance by cytidine deaminase (CDA) in the gut and liver. This dose-escalation study, guided by pharmacokinetic and pharmacodynamic observations, evaluated whether simultaneous oral administration with the novel CDA inhibitor cedazuridine increases decitabine bioavailability for the treatment of myelodysplastic syndromes. Methods: In this phase 1 study, we enrolled patients aged 18 years or older with myelodysplastic syndromes or chronic myelomonocytic leukaemia. Eligible patients were assigned to cohorts to receive escalating oral doses of decitabine and cedazuridine. The starting dose was decitabine 20 mg and cedazuridine 40 mg. Treatment cycles lasted 28 days, with 5 days of drug administration. In cycle 1, each patient received a cohort-defined dose of oral decitabine on day −3, a 1-h intravenous infusion of decitabine 20 mg/m 2 on day 1, and cohort-defined doses of oral decitabine plus cedazuridine on days 2–5. In cycles 2 and beyond, the oral decitabine and cedazuridine were given on days 1–5. The dose of cedazuridine was escalated first and decitabine was escalated once CDA inhibition by cedazuridine approached the maximum effect. The drug dose was escalated if mean decitabine area under the curve (AUC) of the oral drug was less than 90% of that for intravenous decitabine in the cohort and if no dose-limiting toxicity was observed. Dose-limiting toxicity was defined as a grade 3 or greater non-haematologic toxicity or grade 4 haematologic toxicity lasting more than 14 days and unrelated to the underlying disease. Once the decitabine AUC target range set as the primary endpoint, and established with intravenous decitabine, was reached at a dose deemed to be safe, the cohort that most closely approximated intravenous decitabine exposure was expanded to 18 evaluable patients. The primary objectives were to assess the safety of decitabine plus cedazuridine, and to determine the dose of each drug needed to achieve a mean AUC for decitabine exposure similar to that for intravenous decitabine exposure. This study is registered withClinicalTrials.gov, numberNCT02103478 . Findings: Between Oct 28, 2014, and Nov 13, 2015, we enrolled 44 eligible patients (of 75 screened) with previously treated or newly diagnosed myelodysplastic syndromes or chronic myelomonocytic leukaemia; 43 of the enrolled patients were evaluable. Participants were treated in five cohorts: cohorts 1–4 included six evaluable patients each; cohort 5 included 19 patients in a 13-patient expansion. Dose-dependent increases in decitabine AUC and peak plasma concentration occurred with each cohort dose escalation. There was no evident increase in toxicity compared with that reported for intravenous decitabine. Decitabine 30 mg and 40 mg plus cedazuridine 100 mg produced mean day-5 decitabine AUCs (146 ng × h/mL for decitabine 30 mg, and 221 ng × h/mL for decitabine 40 mg) closest to the mean intravenous-decitabine AUC (164 ng × h/mL). The most common grade 3 or more adverse events were thrombocytopenia (18 [41%] of 44 patients), neutropenia (13 [30%]), anaemia (11 [25%]), leukopenia (seven [16%]), febrile neutropenia (seven [16%]), and pneumonia (seven [16%]). Four (9%) patients died because of adverse events, none of which was considered drug related, and three (7%) patients died more than 30 days after discontinuing treatment because of progressive disease (two [5%]) and respiratory failure (one [2%]). Interpretation: Oral decitabine plus cedazuridine emulated the pharmacokinetics of intravenous decitabine, with a similar safety profile and dose-dependent demethylation. Clinical responses were similar to intravenous decitabine treatment for 5 days. Further study of decitabine plus cedazuridine as an alternative to parenteral therapy or in combination with other new oral agents for myeloid disorders is warranted. Funding: Astex Pharmaceuticals, Inc.